Exploring the interplay of innovation competence and chemistry mastery: insights from educational practices and factors of influence - binti Md. Aris, Norliyana; Ibrahim, Nor Hasniza binti; Binti Abd Halim, Noor Dayana; bin Surif, Johari (Eclética Química, 2025)
Innovation competence is a critical skill today, enabling individuals to generate and apply innovative ideas. Its influence on students’ mastery of chemical concepts and the factors shaping this relationship remain underexplored. This scoping review analyzes 31 studies to address three research questions: (1) How does innovation competence influence students’ mastery of chemical concepts? (2) What factors shape this relationship? (3) What strategies can educators implement to foster innovation competence and chemical mastery? Findings reveal a positive correlation between innovation competence and chemical mastery, influenced by motivation, teaching strategies, and curriculum design. Practical strategies include problem-based learning, collaborative projects, and hands-on activities. While these insights provide valuable guidance, further research is needed to fully understand the interplay between innovation competence and chemical learning. This study offers actionable recommendations for enhancing teaching practices and advancing future research in chemistry education.